2020
DOI: 10.1021/acs.jpcc.0c07194
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Size-Dependent Pore Architecture and Surface Chemical Characteristics of Desolvated ZIF-8 Investigated Using Positron Annihilation Spectroscopy

Abstract: Crystal downsizing of zeolitic imidazolate framework-8 (ZIF-8) has been shown to affect the flexibility of its framework, leading to the occurrence of “gate-opening” phenomenon at higher applied gas pressures compared to larger size crystals. In the present study, we have investigated the crystal size-dependent pore architecture of crystalline desolvated ZIF-8 samples which is expected to play the most deterministic role in its gas adsorption behavior. In order to avoid the pressurization or gas molecule–ZIF i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 39 publications
0
23
0
Order By: Relevance
“…Recently, it has been shown that PALS can efficiently probe the pore sizes of ZIFs that are true representation of average pore sizes from a bulk powder samples. Typical PALS spectra of ZIF-67, ZIF-8, and ZIF-7­(np) acquired under vacuum (∼10 –3 mbar) are shown in Figure . PALS spectra clearly show long and distinct o -Ps lifetime components for ZIF-67, ZIF-8, and ZIF-7­(np).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, it has been shown that PALS can efficiently probe the pore sizes of ZIFs that are true representation of average pore sizes from a bulk powder samples. Typical PALS spectra of ZIF-67, ZIF-8, and ZIF-7­(np) acquired under vacuum (∼10 –3 mbar) are shown in Figure . PALS spectra clearly show long and distinct o -Ps lifetime components for ZIF-67, ZIF-8, and ZIF-7­(np).…”
Section: Resultsmentioning
confidence: 99%
“…In the case of ZIF-8 this shifts the gate-opening transition pressure towards higher pressures. In addition, surface blockage and pore network blockage of the interior are identified as contributing factors ( Sharma et al, 2020 ).…”
Section: Adsorption-induced Stressmentioning
confidence: 99%
“…In the present study, we investigated the pore architecture of fully crystalline ZIF-7 x –8 ( x = 6.6–18.2%) and their framework flexibility under a CO 2 pressure up to 10 kg cm –2 using positron annihilation lifetime spectroscopy (PALS). Recently, it has been established that PALS-based methods are highly advantageous for pore architecture investigation of flexible ZIFs and complementary to gas-adsorption-based methods. It is primarily because the PALS-based method is sensitive from ultramicropores to mesopores and the measurements are not affected by any guest–framework-interaction-induced flexibility, which is otherwise the case for gas-adsorption-based methods.…”
Section: Introductionmentioning
confidence: 99%